Upaya Pembinaan Narapidana Melalui Wadah Lembaga Pemasyarakatan - Nila Trisna (Jurnal Community, 2017)
In Law no. 12 of 1995 concerning pemasyarakatan which became a positive law and must be implemented to achieve the purpose of pemasyarakatan. The guidance given to prisoners has a purpose to enable prisoners to play an active role in natural development and to live fairly as good and responsible citizens after their prison term is completed. Coaching is adapted to the talents and interests of prisoners so that the prisoners understand that all coaching is given for their good that they have the readiness to return with the community when they are free. So the inmates rules and follows every coaching well and without feeling compelled. Penitentiary also provides the rights of inmates as part of the community in accordance with the prevailing provisions so as to create a conducive atmosphere. Guidance given in the form of personality coaching that includes religious and moral coaching, self-help include general skills and special skills. This research uses normative juridical method, that is approach which is done by examining the legislation which relevant with the problem which studied or looking from the aspect of sociology of law. Technique of data collection is done by Research of Library (Library Research), that is by studying book and literature relevant with writing. Keywords: Coaching, Prisoners, Prisons